Optimization of Oral Thin Film Cetirizine HCI by Response Surface Methodology: Disintegration and Mechanical Properties - Nining, Nining; Amalia, Anisa; Rahmatullah, Rizki (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Starch is a natural biopolymer used as a film-forming polymer on oral thin film (OTF). Its solubility can increase by modifying enzymes to form maltodextrin (MDX). Sorghum is a potential plant because it contains relatively high starch, 72.3-75.1%. The concentration of film-forming and plasticizers in OTF will significantly affect its disintegration and mechanical properties. This study aimed to obtain the optimal formula for OTF cetirizine HCl based on MDX-sorghum as a film-forming and triethyl citrate as a plasticizer using the Response Surface Methodology (RSM). Sorghum starch was enzymatically modified and characterized physically and mechanically. The formula is optimized based on the disintegration and mechanical properties of the film on the contour plot using Central Composite Design (CCD) in RSM. The percentage error between the predicted and actual values in the response validates the suggested model. The results showed that the production of MDX-sorghum was successful with a characteristic value of dextrose equivalent (DE) 6,3±0,13; swelling power of 2.87; solubility of 52.9%; and a yield of 86.71%. Response data from the 14 formulas obtained include disintegration time of 85-172 seconds, elongation 64.86-109.32%, and tensile strength from 1.4 to 3.57 MPa. The optimal formula suggested a concentration of 4.56% MDX-sorghum and 10% triethyl citrate, with desirability of 0.87. The model validation results show an error percentage of <5%, so the suggested model can be accepted.